Non-educational background teachers’ knowledge of pedagogical competences - Hidayatullah, Heri; Qomariyah, Siti Syafi'atul; Krisnahadi, Tama (International Journal of Evaluation and Research in Education (IJERE), 2024)
The existence of non-educational background teachers (NEBTs) no doubt contributes to developing the quality of education but seems to lack attention. This research aimed to investigating the knowledge of NEBTs on pedagogical competence. A mixed method with explanatory sequential design was employed. The study was conducted in Central Lombok Regency. The total population was 109 spreading in 12 districts and three participants out of the total population were selected to participate in the interview. The instruments were a test in the form of multiple choice and an interview. The data from the test were analyzed quantitatively while the data obtained from the interview was analyzed qualitatively. The data of the test showed that the scores of four sub-aspects of pedagogical competence were 52.20 for the learning theories, 57.33 for students’ characteristics, 61.75 for the nature of education, and 84.30 for curriculum. Thus, the mean score was 63.90. The data from the interview showed that self-development efforts were low and the school supervisors and staffs role contributed only at the practical level. The research concluded that the knowledge of NEBTs was 63.90 in average due to the internal and external factors.